2007
DOI: 10.1063/1.2799148
|View full text |Cite
|
Sign up to set email alerts
|

The elastohydrodynamic force on a sphere near a soft wall

Abstract: The influence of soft boundaries on the forces experienced by a small sphere undergoing slow translation and rotation near a wall is investigated using asymptotic and numerical methods. The clearance between the sphere and the wall is assumed to be small, so that the lubrication approximation holds in the gap. The forces induced by boundary deformation break the symmetry of the Stokes equations, leading to irreversibility of the motion of the sphere and yielding a nonzero lift force. A general formulation, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…which measures the scale of the substrate deformation relative to the fluid gap thickness [45]. In this framework, previous theoretical studies [11][12][13][14][15][16] have shown that for Λ 1 and for given u c and h f the motion of an infinite cylinder is accompanied by the emergence of an elastohydrodynamic lift force F ∼ Λµu c 2 L/h 2 f , which was confirmed experimentally [35]. Since the cylinder also rotates with negligible inertia, the sum of torques due to elastohydrodynamics (induced by the substrate's deformation due to sliding) τ s and viscous damping of the rotational motion τ Ω vanish [36]: τ Ω +τ s = 0.…”
Section: Scaling Arguments and The Finite Size Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…which measures the scale of the substrate deformation relative to the fluid gap thickness [45]. In this framework, previous theoretical studies [11][12][13][14][15][16] have shown that for Λ 1 and for given u c and h f the motion of an infinite cylinder is accompanied by the emergence of an elastohydrodynamic lift force F ∼ Λµu c 2 L/h 2 f , which was confirmed experimentally [35]. Since the cylinder also rotates with negligible inertia, the sum of torques due to elastohydrodynamics (induced by the substrate's deformation due to sliding) τ s and viscous damping of the rotational motion τ Ω vanish [36]: τ Ω +τ s = 0.…”
Section: Scaling Arguments and The Finite Size Effectmentioning
confidence: 99%
“…Often, this elastohydrodynamic coupling is seen in the presence of confined flow where pressure gradients are likely to be large. Previous theoretical works have studied confined flows in the soft lubrication approximation and accounted for the roles of elasticity [11][12][13][14][15][16], fluid compressibility [17], the inertia of the fluid and the elastic medium [18], and viscoelasticity of the substrate [19]. More recent works have focused on elastohydrodynamic effects for liquids confined at the micro and nano scales [20][21][22], which has important consequences for surface mechanical characterization [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This result is relaxed when the interacting surfaces are rough, the fluid is compressible, or when either or both surfaces are compliant. [2][3][4][5] A finite force at contact has also been shown to occur when the solid…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6 In the limiting case of small elastic deformations, the problem can be solved perturbatively and reduces to a set of ordinary differential equations. 2,3,7 For the opposite case of strong deformations, the contact area becomes flat as in a classical Hertzian contact, 8 except for the effect of the thin lubrication layer. [9][10][11] Here we show that at the edge of the contact area, the film thickness is described by a similarity solution, whose shape is governed by an integro-differential equation, as opposed to the ordinary differential equations encountered in most singular fluid problems.…”
mentioning
confidence: 99%